Clinical Pharmacology in Denmark in 2016 – 40 Years with the Danish Society of Clinical Pharmacology and 20 Years as a Medical Speciality. Issue 6 (23rd October 2016) - Brøsen, Kim; Andersen, Stig Ejdrup; Borregaard, Jeanett; Christensen, Hanne Rolighed; Christensen, Palle Mark; Dalhoff, Kim Peder; Damkier, Per; Hallas, Jesper; Heisterberg, Jens; Jessen, Niels; Jürgens, Gesche; Kampmann, Jens Peter Konnerup; et al.
Abstract: The Danish Society of Clinical Pharmacology was founded in 1976, and mainly thanks to the persistent efforts of the society, clinical pharmacology became an independent medical speciality in Denmark in 1996. Since then, clinical pharmacology has gone from strength to strength. In the Danish healthcare system, clinical pharmacology has established itself as an indispensible part of the efforts to promote the rational, safe and economic use of drugs. Clinical pharmacologists are active in drug committees both in hospitals and in the primary sector. All clinical pharmacology centres offer a local medicines information service. Some centres have established an adverse drug effect manager function. Only one centre offers a therapeutic drug monitoring service. Clinical pharmacologists are responsible for the toxicological advice at the Danish Poison Information Centre at Bispebjerg University Hospital in the Capital Region. The Department of Clinical Pharmacology at Aarhus University Hospital works closely together with forensic toxicologists and pathologists, covering issues regarding illicit substances, forensic pharmacology, post‐mortem toxicology, expert testimony and research. Therapeutic geriatric and psychiatric teach‐inns for specialist and junior doctors are among the newest initiatives organized by clinical pharmacologists. Clinical pharmacologists work also in the Danish Medicines Agency and in the Danish pharmaceutical industry, and the latter has in particular a great growth potential for creating new jobs and career opportunities for clinical pharmacologists. As of July 2016, the Danish Society of Clinical Pharmacology has 175 members, and 70 of these are specialists in clinical pharmacology corresponding to approximately 2.5 specialists per 1000 doctors (Denmark has in total 28, 000 doctors) or approximately 12 specialists per one million inhabitants.